The effect of price perceptions, service quality, and brand image on purchasing decisions on JNE Expedition Services - Rut Laura Silalahi; Adi Suparwo (Trigin Publisher, 2023)
The current shift in society's shopping style which is dominated online requires a service so that the seller's product reaches the buyer's hands and this is called an expedition. This research is aimed at determining the influence of price perceptions, service quality and brand image on decisions to purchase services on JNE expeditions in the city of Bandung. The research was conducted using quantitative research methods with descriptive and verification approaches. The data in this research comes from primary data and secondary data, while data collection techniques were carried out by means of interviews and questionnaires. The sampling technique used purposive sampling, with a sample size of 100 respondents determined using the Slovin formula. Based on data processing, the results obtained show that both partial and simultaneous perceptions of price, service quality and brand image on purchasing decisions have a positive and significant influence. In this research, the difference is that no researcher has discussed the influence of price perception, service quality and brand image on purchasing decisions on JNE Bandung expeditions. Apart from that, in this research, the brand image variable partially has a greater influence on purchasing decisions than the price perception and service quality variables